Local Time Dependence of the Thermal Structure in the Venusian Equatorial Upper Atmosphere: Comparison of Akatsuki Radio Occultation Measurements and GCM Results. Issue 9 (6th September 2018) - Ando, Hiroki; Takagi, Masahiro; Fukuhara, Tetsuya; Imamura, Takeshi; Sugimoto, Norihiko; Sagawa, Hideo; Noguchi, Katsuyuki; Tellmann, Silvia; Pätzold, Martin; Häusler, Bernd; Murata, Yasuhiro; Takeuchi, Hiroshi; et al.
Abstract: Temperature profiles of the Venus atmosphere obtained by the Akatsuki radio occultation measurements showed a prominent local time dependence above 65‐km altitude at low latitudes equatorward of 35°. A zonal wavenumber 2 component is predominant in the temperature field, and its phase (i.e., isothermal) surfaces descend with local time, suggesting its downward phase propagation. A general circulation model (GCM) for the Venus atmosphere, AFES‐Venus, reproduced the local time‐dependent thermal structure qualitatively consistent with the radio occultation measurements. Based on a comparison between the radio occultation measurements and the GCM results, the observed zonal wavenumber 2 structure is attributed to the semidiurnal tide. Applying the dispersion relationship for internal gravity waves to the observed wave structure, the zonally averaged zonal wind speed at 75‐ to 85‐km altitudes was found to be significantly smaller than that at the cloud top. The decrease of the zonal wind speed with altitude is attributed to the momentum deposition by the upwardly propagating semidiurnal tide excited in the cloud layer. Plain Language Summary: Akatsuki radio occultation measurements showed the local time dependence of the Venus atmosphere in the equatorial region. By comparing the measurements with a general circulation model, it is attributed to the upward propagating semidiurnal tide generated in the cloud layer. And then, we proposed a new method to estimate the zonal wind speed above the cloud layer, where any optical instruments cannot be measured, for the first time. Key Points: Akatsuki RO measurements show the local time dependence of the thermal structure of the Venus upper atmosphere in the equatorial region Comparison of RO measurements and the GCM suggests the importance of semidiurnal tide to the local time dependency A new method to estimate the zonal wind speed in the upper atmosphere in the equatorial region is proposed